2022
DOI: 10.3390/bioengineering9100589
|View full text |Cite
|
Sign up to set email alerts
|

Proteo-Molecular Investigation of Cultivated Rice, Wild Rice, and Barley Provides Clues of Defense Responses against Rhizoctonia solani Infection

Abstract: Rhizoctonia solani is a soil-borne fungus causing sheath blight disease in cereal crops including rice. Genetic resistance to sheath blight disease in cereal crops is not well understood in most of the host(s). Aside from this, a comparative study on the different hosts at the biochemical and proteomic level upon R. solani infection was not reported earlier. Here, we performed proteomic based analysis and studied defense pathways among cultivated rice (cv. Pusa Basmati-1), wild rice accession (Oryza grandiglum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
(79 reference statements)
1
2
0
Order By: Relevance
“…The results and several physiological indices demonstrated that the antioxidative enzyme-related gene or protein is up-regulated at the transcriptional and translational levels. This finding corresponds with the results of omics studies on resistant cultivated rice, wild rice, and barley after Rhizoctonia solani infection ( Shamim et al., 2022 ). Furthermore, M. oryzae infection increases ROS production in MWG, stimulating antioxidant enzymes to counteract oxidative damage and detoxify ROS.…”
Section: Discussionsupporting
confidence: 89%
“…The results and several physiological indices demonstrated that the antioxidative enzyme-related gene or protein is up-regulated at the transcriptional and translational levels. This finding corresponds with the results of omics studies on resistant cultivated rice, wild rice, and barley after Rhizoctonia solani infection ( Shamim et al., 2022 ). Furthermore, M. oryzae infection increases ROS production in MWG, stimulating antioxidant enzymes to counteract oxidative damage and detoxify ROS.…”
Section: Discussionsupporting
confidence: 89%
“…Fourteen defense genes i.e. chitinase, gibberellin signal transduction and NBS-LRR encoding genes were present in the QTL regions qShB5.1, qShB5.2 that were reported to be responsible for ShB resistance in transgenic rice plant (Baisakh et (Shamim et al 2022). In conclusion, the study has identi ed the important QTLs and underlying candidate genes that might play important role in further understanding genetics of sheath blight resistance in rice and development of sheath blight resistant cultivars.…”
Section: Discussionmentioning
confidence: 89%
“…was inoculated against sheath blight disease that increase in the chlorophyll content of leaves was observed (Tamreihao et al 2016). The studies in sheath blight disease based on iTRAQ based proteomics to identify the major mechanisms of resistant varieties against sheath blight showed that increased expression of chlorophyl a-b binding protein 2 during the R. solani infection in resistant varieties (Feng et al 2022, Shamim et al 2022). The resistant varieties thus tends to increase chlorophyll content under sheath blight pathogen infection, which correlated well with our results that S. hyderabadensis inoculation increased the expression of chlorophyll a-b binding protein 2.…”
Section: Discussionmentioning
confidence: 99%